Perspectives of Students at Institutions of Higher Education Toward Open Distance Learning - Abd Aziz, Noriza; Abu Bakar, Nashirah; Abdul Aziz, Ibrahim; Md Hussain, Muhammad Nasri; Ishak, Nor Syahidah (Asian Scholars Network, 2023)
Open and Distance Learning (ODL) is a way of learning remotely without being in regular face-to-face contact with an instructor in the classroom. Students learn the content using instructional materials that are uploaded on online platforms. Despite the convenience of the learning method, there is a need to assess students' awareness and intention to use these platforms. This paper evaluates whether perceived usefulness (PU), perceived ease of use (PEU), and perceived self-efficacy (PSE) can influence students enrolled at an institution of higher education (IHE) to choose open distance learning (ODL). The Technology Acceptance Model (TAM) has been identified to support the research framework of this study. A research framework was proposed and three hypotheses were developed. Data were obtained from 125 respondents enrolled in the ODL Program using convenient sampling. Data were analyzed using the SPSS statistical program on descriptive statistics, factor analysis, and regression. The results revealed that PU and PSE have direct relationships with the behavioral intention to choose ODL. Therefore, PU and PSE influenced the students to choose ODL. Meanwhile, PEU has no direct relationship with behavioral intention to choose ODL. Therefore, PEU cannot attract the interest and attention to influence the students to use ODL. The study helped uncover a significant understanding of students’ acceptance of ODL for IHEs to develop further ODL programs related to Islamic Finance and Banking courses under Massive Open Online Courses (MOOC). Also, ODL provides opportunities for interactions and communications between students and lecturers through information and communication technology (ICT) and multimedia. This study provides further empirical support that behavioral intention is able to be influenced to choose ODL